The effect of internet addiction on students' emotional and academic performance / Sylvia Nabila Azwa Ambad, Khairiah Mazdiah Kalimin and Ku Mohd Amir Aizat Ku Yusof - Azwa Ambad, Sylvia Nabila; Kalimin, Khairiah Mazdiah; Ku Yusof, Ku Mohd Amir Aizat (2017)
In this digital age, the internet revolution substantially affected people's life. Education, economics, politics, and social fields are greatly influenced by the internet. The internet dependency has a positive and negative impact on people. For students, the teaching and learning have become easier compared to the olden days as nowadays information is at their fingertips. Despite its benefits, internet addiction may negatively impact the students' life such as on their emotional instability, depression, poor time management, and poor academic performance. Therefore, the aim of the present study is to determine the effect of internet addiction to students' academic performance and emotional instability. The emotional effect on the academic performance was also analysed. This study was conducted among 280 diploma students in UiTM, Sabah. A Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0 was used to analyse the data. The results revealed all hypotheses formulated were significantly related. The results revealed all hypotheses formulated were significantly related which the results indicated that internet addiction has a positive relationship with students' emotional instability. Then, the students' emotional instability translated to a poor academic performance and the internet addiction also has a negative relationship with the students' academic performance. The empirical findings of this study will be of great significance to the followings; the lecturers and university can utilise the findings as guidelines to formulate new policy regarding internet use on campus, the results of this study can serve as a reminder and create awareness to the parents, to better control their children's internet access such as cutting the budget for broadband allowance and continuous monitoring, and can serve as an eye opener to students on negative effects of internet excessive use, thus, the students need to wisely use the internet for educational purposes.